PENGARUH KOMPOS DAUN LAMTORO (Leucaena leucocephala) TERHADAP PERTUMBUHAN SEMAI CEMPAKA KUNING (Michelia champaca L) - s, Sulham; Wulandari, Retno (Universitas Tadulako, 2019)
One way to produce good seedlings is to use appropriate media for seedling growth so that they can produce healthy seedlings with optimal growth. The use of soil mixed with organic matter compost of Lamtoro (Leucaena leucocephala) leaves with certain amounts is expected to increase the growth of Yellow Cempaka seedlings (Michelia champaca L). This study aims to determine the effect of various doses of compost of Lamtoro (Leucaena leucocephala) media on the growth of yellow Cempaka (Michelia Champaca L) seedlings. The research was carried out for three months, namely from February to May 2019, at the BPDAS Palu-Poso Permanent Nursery, Tadulako University, Palu. The study used a Completely Randomized Design (CRD) consisting of 4 treatments namely L0 = soil (control), L1 = soil and lamtoro leaf compost 1: 1, L2 = soil and leaf compost Lamtoro 1: 1/2, L3 = soil and compost Lamtoro leaf 1: 1/3. The parameters observed were height increase, an increase in the number of leaves, an increase in diameter and robustness of seedlings. Data analysis using analysis of variance (F-Test). The results showed that the different doses of compost of Lamtoro (Leucaena leucocephala L) leave had a very significant effect on height increase, increase in the number of leaves of seedling robustness and had no significant effect on seedling stem diameter. The soil treatment and 1:1/2 lamtoro leaf compost (L2) gave the best effect on the growth namely height increase (4.18 cm), leaf number increase (4.2 strands), and robustness of seedlings (93.71).